Did wage inequality increase in Portugal? Yes, and for good reasons - Pereira, João Manuel (2021)
As in Anglo-Saxon countries, wage inequality increased in Portugal from the beginning of the 1980s to the end of the 2000s. Using data from a matched employer-employee data set and reweighting methods, we show that the increased wage inequality in Portugal is fundamentally explained by compositional